ROLE OF SERVICE QUALITY IN CUSTOMER SATISFACTION: A COMPARATIVE ANALYSIS OF PRIVATE AND PUBLIC SECTOR BANKS IN INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The performance of banks can be measured by  providing quality service to the customers in  order to achieve competitive edge. The level  of customer satisfaction can be determined  through the quality of product or services  provided to the customers and it is believed  that satisfied customers develop and maintain  relationship with the organization and purchase  more products or services regularly than the  dissatisfied customers. The purpose of this  paper is to examine the impact of various  service quality variables on the level of customer  satisfaction and compare the private and public  sector banks using a sample from Delhi NCR.  The sample is consisting of responses from  240 customers of public sector banks and 238  customers of private sector banks. Forward  stepwise regression was used for the purpose  of analysis. The results indicated that in case  of private sector banks, well managed policies  for transactions security, employees’ courtesy  with the customers, personalized services to  customers, bank’s commitment towards the  customers, have positive impact on customer  satisfaction. On the other hand, in case of  public sector banks, commitment towards the  customers, accuracy of account information,  and information about the new and attractive  schemes and suggestion for the best possible  course of action have positive impact on  customer satisfaction.
Keywords: Service Quality; Customer Satisfaction; Forward Stepwise regression; private sector banks; public sector banks